Multiple tipping points and optimal repairing in interacting networks - Antonio Majdandzic (Nature Portfolio, 2016)
Systems composed of many interacting dynamic networks exhibit complicated collective dynamics. Here, the authors study failure, damage spread and recovery in two interacting networks, constructing the phase diagram and revealing the role of triple points for optimal damage repair.